LEKSIKON PADA TRADISI NAIK TOJANG DAN GUNTING RAMBUTMASYARAKAT SUKU BUGIS DESA OLAK-OLAK KUBU KECAMATANKUBUKABUPATEN KUBU RAYA - Nindiva, Muthia; Madeten, Sisilya Saman; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study discusses the problem of lexicon shape, lexical meaning, and cultural meaning found in the tradition of NaikTojang and Hair Scissors of Olak-Olak Kubu Village, KubuDistrict, Kubu Raya Regency. The purpose of this study istodescribe the lexicon of tools, materials, and processes inthetradition of Naik Tojang and Hair Scissors, and describe thembased on lexical meaning and cultural meaning. The methodused in this study is a descriptive method with a qualitativeform. The source of data in this study is the Olak-Olak Kubuvillage community using observation, interview, record, andrecording techniques. This research resulted in 18 formsof lexicons of tools and materials used in the Naik Tojangtradition consisting of 9 lexicons of tools and 9 lexiconsof materials, then there were 15 forms of lexicons of tools andmaterials used in the Hair Scissors tradition consisting of 2lexicons of tools and 13 lexicons of materials, then there were6 processes carried out in the Naik Tojang tradition, and thereare 6 processes carried out in the Hair Scissors tradition.